Filmes nanoestruturados para detecção do antígeno prostático específico utilizando nanopartículas de ouro - Camilo, Douglas Eleutério (2019)
In the present work, nanostructured films were prepared through the self-assembly techniques for the detection of prostatic specific antigen (PSA), a glycoprotein produced in abnormal levels in case of prostate cancer. Two self-assembly approaches were used: the self-assembled monolayer (SAM) technique for the substrate functionalization and the layer-by-layer (LbL) technique for the building of the sensing unit. The specific antibody to PSA (anti-PSA) was immobilized on the gold nanoparticles surface (AuNP-antiPSA conjugate) for later assembly by the LbL technique. The AuNPs-anti-PSA conjugate was characterized by ultraviolet-visible spectroscopy indicating absorption bands at 520 and 260 nm related to the AuNP plasmons absorption and anti-PSA tryptophan absorption, respectively. The fluorescence spectrum presented a band at 367 nm attributed to the emission of tryptophan fluorescence present in the anti-PSA. The morphology analysis of AuNPs by Transmission Electron Microscopy (MET) provided an estimated average diameter of 3.5 ± 0.9 nm. The films were fabricated on gold (Au) covered glass slides previously cleaned and functionalized with 11-mercaptoundecanoic acid (11-MUA). The LbL films were prepared by the sequential adsorption of nanostructured layers of poly(ethyleneimine) (PEI), poly(vinylsulfonic acid, sodium salt) (PVS) and PEI, on the Au functionalized surface. Cyclic voltammetry (VC) confirmed the adsorption of the layers by the reduction of the current peak of Fe(II)/Fe(III) redox probe. Subsequently, bovine serum albumin (BSA) was used to block the non-specific binding sites. Detection was performed with different concentrations of PSA (0.1, 0.5, 1,0, 4,0, 8,0, 10 and 20 ng mL-1) using Electrochemical Impedance Spectroscopy (EIS). The architecture Au/11-MUA/PEI-PVS-PEI/AuNPs-anti-PSA/BSA/PSA was also characterized by Polarization-Modulation Infrared Reflection-Absorption Spectroscopy (PM-IRRAS) to investigate the interaction between the materials, as well as the interaction between antigen and antibody. The high selectivity of the immunosensor was tested by the exposure of the sensor to a non-specific immunoglobulin G (IgG). The limit of detection (LD) and the range of detection obtained by EIS were 0.17 ng mL-1 and 0.1-20 ng mL-1, respectively. The experiments demonstrated that the LbL technique and the use of AuNPs were suitable for the construction of an immunosensor of low cost, rapid development and high sensitivity. Thus, the fabricated immunoassay exhibits high potential for use in the diagnosis of the early stages of prostate cancer.